Nitric oxide function in atherosclerosis - K. E. Matthys; H. Bult (Mediators of Inflammation)
Atherosclerosis is a chronic inflammatory process in the intima of conduit arteries, which disturbs the endothelium-dependent regulation of the vascular tone by the labile liposoluble radical nitric oxide (NO) formed by the constitutive endothelial nitric oxide synthase (eNOS). This defect predisposes to coronary vasospasm and cardiac ischaemia, with anginal pain as the typical clinical manifestation. It is now appreciated that endothelial dysfunction is an early event in atherogenesis and that it may also involve the microcirculation, in which atherosclerotic lesions do not develop. On the other hand, the inflammatory environment in atherosclerotic plaques may result in the expression of the inducible NO synthase (iNOS) isozyme. Whether the dysfunction in endothelial NO production is causal to, or the result of, atherosclerotic lesion formation is still highly debated. Most evidence supports the hypothesis that constitutive endothelial NO release protects against atherogenesis e.g. by preventing smooth muscle cell proliferation and leukocyte adhesion. Nitric oxide generated by the inducible isozyme may be beneficial by replacing the failing endothelial production but excessive release may damage the vascular wall cells, especially in combination with reactive oxygen intermediates.